An economic alternative to the c chart. (1st January 2014) - Black, Ryan; Chimka, Justin R.
An economic alternative to the c chart is described as a statistical model of upward shift from c 0 to c 1, and costs of the two charts are compared in theory. For a range of c chart costs the savings associated with economic design increase linearly.